Caught in the moment: Are there person-specific associations between momentary procrastination and passively measured smartphone use?. (January 2022) - Aalbers, George; vanden Abeele, Mariek M. P.; Hendrickson, Andrew T.; de Marez, Lieven; Keijsers, Loes
Procrastination is an increasingly prevalent phenomenon. Although research suggests smartphones might be involved, little is known about the momentary association between different patterns of smartphone use and procrastination. In a preregistered study, 221 students ( M age = 20, 55% female) self-reported procrastination five times a day for 30 days (i.e., experience sampling method) while their smartphone use was continuously monitored (i.e., passive logging). Using dynamic structural equation modeling on 27, 151 observations, we estimated momentary within-person associations between procrastination and (a) total smartphone use and use of specific application categories (social media, messaging, browsers, games, and video streaming), (b) notifications, and (c) smartphone use fragmentation. Procrastination was positively albeit weakly associated with all aforementioned patterns, and associations varied from person to person. Collectively, our findings suggest these popular devices potentially encourage dilatory behavior.